Maqāṣid al-Sharī’ah on Wakaf System - Heru Susanto (Hunafa: Jurnal Studia Islamika, 2017)
The main purpose of the shariah is realizing the benefit in order to maintain the shariah’s purposes. There are three level of human’s basic necessity: primary (ḍarūriyyāt), secondary (hājiyyāt), and tertiary (taḥsīniyyāt). The human’s basic necessity is divided into five, first, protection of religion (ḥifẓ al-dīn), second, protection of life (ḥifẓ al-nafs), third, protection of mind (ḥifẓ al-‘aql), fourth, protection of the offspring (ḥifẓ al-nasl), and fifth, protection of property (ḥifẓ al-māl). So it can be said that the aims of shariah can be achieved by fulfilling these five basic necessities of human beings. Waqf as one of the Islamic filantrophies has a big role and purpose to realize the benefit of human being, that is realizing the prosperity reflected by the fulfilment of human’s basic needs in accordance with the goals of shariah be it primary, secondary and tertiary.